Marriage economics, bargaining and strategic agency: Egyptian-Syrian intermarriage practices in the context of displacement - Dina M. Taha (21797186) (2024)
Based on forty-eight qualitative interviews with Syrian refugee women and their families, this study explores the dynamics of Syrian-Egyptian marriages formed after displacement. Grounded in acculturation, marriage economics, and social exchange theories, I ask: what role is played by both cultural customs and displacement in dictating the Egyptian-(displaced)Syrian intermarriage trajectories and power dynamics in these unions? And how did Syrian women and Egyptian men leverage cultural differences to maximize their own benefits? The results outline how urfi (customary) marriage and marriage economic traditions differ between these two often homogenized (and continuously Orientalized) cultures, impacting the marital relationship’s nature, bargaining power and success. Beyond the passive exploitation narrative that hounds these highly stigmatized arrangements, the analysis illuminates how these marriages are often a result of immediate utilitarian and financial intersecting interests between the men and the women, they still carry long-term effects influencing the spousal balance of power. Nonetheless, some Syrian women leveraged cultural differences to maximize their gains and mitigate the implications of displacement and uprooting demonstrating a strategic and dialogical acculturation. The study concludes by highlighting the impact of displacement on marriage dynamics, shedding light on financial and power imbalances while highlighting how social and moral factors such as family support and socioeconomic factors influence the marriage dynamic. Contribution: The study sheds light on inter-Arab marriages in displacement contexts and broadens understanding within the larger spectrum of Arab marital dynamics, stimulating nuanced conversations about the sociology of marriage and family in the Arab world. Other Information Published in: International Journal of Intercultural Relations License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijintrel.2024.101995